Dr. Ivan Tavčar – odvetnik, ki se ni nikoli upokojil - Čeferin, Peter (Pravnik, 2023)
We all know Ivan Tavčar, PhD, as a writer, many as a politician, but few as a lawyer, although he was a lawyer all his life and he never retired. Contemporaries called his law firm a “fortress of liberalism”. Because Ivan Tavčar stood for economic, religious, political, and ideological freedom of the individual. He stood for fundamental ideas such as the constitution, liberal democracy, free and fair elections, human rights, and freedom of religion. He stood for the equality of all people, for equality before the law and for the autonomy of nations. The title of the academy, at which the author presented this text as a speaker, is therefore somewhat appropriate: “Let’s look up to Tavčar!”
Keywords: Avstro-Ogrska; človekove pravice; enakopravnost; liberalizem; osebna svoboda; slovenski odvetniki; slovenski pisatelji; slovenski politiki; Tavčar, Ivan